(untitled) (LEGAL DIALOGICA, 2025)
This study aims to examine the legal basis for the determination of suspects in the criminal act of damaging campaign props (APK) and to identify its implications for the legal subjects designated as suspects. The research employs an empirical legal method with a qualitative approach, conducted through literature review and interviews with the Gowa Resort Police as a case study. The primary legal sources used include the Indonesian Criminal Code (KUHP), Law No. 7 of 2017 on General Elections, and provisions of criminal procedural law. The research findings indicate that the determination of suspects in the case of damaging Campaign Props (APK) is based on the provisions of Article 280 in conjunction with Article 521 of the Election Law, referring to the evidentiary procedures outlined in the Criminal Procedure Code (KUHAP). In the case that occurred in Gowa Regency, the suspect was designated after sufficient preliminary evidence was obtained, including video recordings and a report from the complainant. The Gakkumdu Center played an active role in this process to ensure coordination between Bawaslu, the Police, and the Prosecutor’s Office. This study concludes that although the legal basis for suspect designation is fairly clear, its implementation still requires strengthening — in terms of regulation, inter-agency coordination, and public awareness. A stronger commitment is needed from law enforcement agencies and election organizers to enforce the rules fairly and transparently in order to uphold the quality of democracy in Indonesia. Abstrak: Penelitian ini bertujuan untuk mengkaji dasar hukum penetapan tersangka dalam tindak pidana pengrusakan APK serta untuk mengidentifikasi implikasinya terhadap subjek hukum yang ditetapkan sebagai tersangka. Metode hukum empiris, dengan pendekatan kualitatif, melalui studi pustaka dan wawancara dengan pihak Kepolisian Resor Gowa sebagai studi kasus. Sumber hukum utama yang digunakan adalah KUHP, UU No. 7 Tahun 2017 tentang Pemilu, serta ketentuan hukum acara pidana.Hasil penelitian Hasil penelitian menunjukkan bahwa penetapan tersangka atas pengrusakan Alat Peraga Kampanye dilakukan berdasarkan ketentuan Pasal 280 jo. Pasal 521 UU Pemilu, dengan mengacu pada prosedur pembuktian sebagaimana diatur dalam KUHAP. Dalam kasus yang terjadi di Kabupaten Gowa, penetapan tersangka dilakukan setelah diperoleh bukti permulaan yang cukup, termasuk rekaman video dan laporan dari pihak pelapor. Sentra Gakkumdu berperan aktif dalam proses ini untuk menjamin koordinasi antara Bawaslu, Kepolisian, dan Kejaksaan.Penelitian ini menyimpulkan bahwa meskipun dasar hukum penetapan tersangka sudah cukup jelas, implementasinya masih memerlukan penguatan, baik dari sisi regulasi, koordinasi antar lembaga, maupun kesadaran masyarakat. Diperlukan komitmen yang lebih kuat dari aparat penegak hukum dan penyelenggara pemilu untuk menegakkan aturan secara adil dan transparan demi menjaga kualitas demokrasi di Indonesia.